Distribution of electronic states in amorphous Zn-P thin films on the basis of optical measurements - Jarząbek, Bożena; Weszka, Jan; Cisowski, Jan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Transmission and fundamental reflectivity studies, completed on amorphous Zn-P thin films, allowed us to obtain parameters describing the fundamental absorption edge, i.e., the optical pseudogap EG, Urbach energy EU and exponential edge parameter ET. All these data, together with the results of earlier transport measurements, have been utilized in developing simple models of electronic structure (distribution of electronic states) for amorphous Zn-P thin films of two compositions, i.e., Zn57P43 (near stoichiometry of Zn3P2) and Zn32P68 (near stoichiometry of ZnP2).
Optica Applicata, Vol. 38, 2008, nr 3, s. 575-583
Keywords: optyka; amorphous semiconductors; thin films; absorption coefficient; model of electronic structure